POWER ANALYSIS OF FORESTRY CUTTERS FOR COMMINUTING OF WOOD WASTE IN POPLAR CLEARINGS. PART 1: ENERGY INTENSITY (Innovation in Woodworking Industry and Engineering design, 2026)
Forestry milling cutters are increasingly used in modern forest technologies for soil preparation of reforestation. In forestry in Bulgaria, although more limited, there is a tendency for introduction of this kind of machinery. Milling machines have good technological qualities, but they also have some drawbacks, such as high-energy consumption and the need of more power drive. In the present work, an experimental study to determine the energy intensity of PT-400 forest milling unit with FAE-300S multifunctional forestry tiller for comminuting of left slash in poplar clearings, was carried out. Based on the results, regression models were developed to express the energy intensity of the forestry cutter, depending on the operating conditions and speed modes of the milling unit. In conclusion, under certain operating conditions, the optimal technological regimes for the operation of the forest mills are defined.